Validity Of Hadith Ru‘yah ‘Al-Ṣādiqah: Implementation of Hadith Exegesis in the Encounter of Sufi Order Guides with Prophet Muhammad SAW through Dreams - Suyuti, Machmud (Jurnal Kajian Manajemen Dakwah, 2023)
This article examines the significance of the Qur'an and Hadith as fundamental sources of Islamic teachings, focusing specifically on the concept of ru‘yah ‘al-ṣādiqah (true dream) within the context of Sufi orders. The Hadith, serving as an explanation of the Qur'an, plays a critical role in comprehensively understanding Islamic teachings. This research particularly highlights the importance of syarḥ al-ḥadiṡ bi al-ḥadiṡ, the practice of interpreting one Hadith with another, to understand the concept of ru‘yah ‘al-ṣādiqah. In the realm of Sufi orders, ru‘yah ‘al-ṣādiqah is interpreted as a meeting with Prophet Muhammad SAW in a dream, a prerequisite for a mursyid (spiritual guide) to authorize the practice of Sufi order rituals to their disciples. The continuity of sanad (the teaching chain) from a mursyid to the Prophet is considered evidence of authenticity and blessing. The Forum Bahsul Masail Multaqa Sufi Ṭariqiyah al-Alami al-Rābi’ affirmed that meeting the Prophet through dreams or in a conscious state is a requirement for a Sufi order mursyid. The experience of waliyullah dreaming of meeting Prophet Muhammad SAW is acknowledged as a truth and a requisite for a Sufi order mursyid. This emphasizes the presence of ittiṣāl al-sanad (connectivity of the teaching chain) within the Sufi order domain. This study hypothesizes that accurate understanding of the Hadith ru‘yah ‘al-ṣādiqah and the encounters of the Prophet with mursyid through dreams are key in validating the practices and teachings within Sufi orders.